Study of causative factors and clinical patterns of periorbital pigmentation - Vibhu Mendiratta; Shiwangi Rana; Rubina Jassi; Ram Chander (Wolters Kluwer Medknow Publications, 2019)
Introduction: Periorbital hyperpigmentation (POH) is one of the common conditions seen in outpatient department. Despite of its huge prevalence, clinical data regarding its etiology and associations are still insufficient. Materials and Methods: We conducted a clinico-investigational study in 50 patients of periorbital pigmentation. A detailed clinical history was recorded, clinical examination and laboratory investigation including complete blood count, vitamin B12 level, and thyroid profile are done. Results: The mean age of the patients presenting with periorbital hyperpigmentation was 29.5 years, out of 50 patients 42 (84%) were females and 8 (16%) were males. About 14% patients give positive family history of POH, history of atopy was positive in 30% of patients. History of various other habits like lack of adequate sleep, prolonged exposure to computers, rubbing eyes, and application of various cosmetics were also found to be positive in these patients. The other associated clinical findings were freckles (12%), telengectesia (2%), erythema (2%), and melasma (2%). In maximum (90%) number of patients, both upper and lower eyelids were involved and pigmentation involving >1 cm of eyelid margin was seen in 62% of patients. Laboratory investigations showed anemia in 10% of patients and low serum vitamin B12 in 12%; however, none of the patients has deranged thyroid profile. Conclusion: POH has a multifactorial etiology and role of correcting various faulty habits is important factor in its management. Presence of anemia and low serum vitamin B12 levels also points toward need of detailed laboratory evaluation in these patients.